2000
DOI: 10.1086/315470
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with aPseudomonas aeruginosaElastase Peptide Reduces Severity of Experimental Lung Infections Due toP. aeruginosaorBurkholderia cepacia

Abstract: Pseudomonas aeruginosa and Burkholderia cepacia produce metalloproteases that effect lung injury. Two epitopes (peptides 15 and 42) previously identified on P. aeruginosa elastase induce the production of antibodies that neutralize protease activity. The effects of immunization with synthetic peptides based on these epitopes on experimental lung infections due to P. aeruginosa or B. cepacia were examined. Rats were immunized with peptides conjugated to keyhole limpet hemocyanin or tetanus toxoid before infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…In vitro assays demonstrate that PSCP is capable of cleaving biologically relevant substrates, including collagen (McKevitt et al, 1989), human IgA, IgG, IgM, transferrin and lactoferrin (C. Kooi & P. A. Sokol, unpublished observation). Previously, we have demonstrated a possible role for the extracellular zinc metalloprotease, PSCP, in B. cepacia virulence (Sokol et al, 2000). In this study, we demonstrate that the expression of a thermolysin-like protease by B. cepacia K56-2 contributes to virulence in an agar bead model of lung infection.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In vitro assays demonstrate that PSCP is capable of cleaving biologically relevant substrates, including collagen (McKevitt et al, 1989), human IgA, IgG, IgM, transferrin and lactoferrin (C. Kooi & P. A. Sokol, unpublished observation). Previously, we have demonstrated a possible role for the extracellular zinc metalloprotease, PSCP, in B. cepacia virulence (Sokol et al, 2000). In this study, we demonstrate that the expression of a thermolysin-like protease by B. cepacia K56-2 contributes to virulence in an agar bead model of lung infection.…”
Section: Discussionsupporting
confidence: 56%
“…McKevitt et al (1989) demonstrated that purified PSCP induces bronchopneumonia in rat lungs characterized by polymorphonuclear leukocyte infiltration and proteinaceous exudate in the airways. Immunization with a peptide corresponding to a conserved zinc metalloprotease epitope significantly decreased the severity of experimental B. cepacia lung infections (Sokol et al, 2000). Further study of the role of extracellular proteases in the pathogenesis of B. cepacia infections has been limited by the lack of isogenic protease mutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutralizing monoclonal antibodies (MAbs) raised against ZmpA cross-react with a Pseudomonas aeruginosa LasB epitope (25,26). Immunization with a peptide ( 341 HGFTEQNG 349 ) corresponding to this conserved P. aeruginosa LasB epitope significantly decreases the severity of experimental B. cenocepacia lung infections (48). Although there is evidence from animal infection models that ZmpA plays a major role in the virulence of B. cenocepacia, the direct role of ZmpA in B. cenocepacia pathogenesis is not understood.…”
mentioning
confidence: 99%
“…Several murine models of B. cepacia infection have been developed (8,42,44), and B. cepacia has been reported in mixed culture with other bacteria in clinical specimens from horses with pneumonia (7) and in specific-pathogen-free piglets (40) and as the sole organism involved in a case of vegetative endocarditis in a horse (47). In this report, we describe an epidemic outbreak of subclinical mastitis associated with infection by the B. cepacia complex in a large flock of dairy sheep.…”
mentioning
confidence: 99%